TEACHING DRAMA IN A HYBRID CLASS - Mulatsih, Maria Vincentia Eka (IJIET (International Journal of Indonesian Education and Teaching), 2023)
Although drama is meant to be performed, due to the pandemic situation, it cannot be done. Beside a government regulation about the maximum number of people who gather in a class or a room, the variants of Covid-19 virus are not easily handled. But still, educators should conduct their learning process well. Some universities in Indonesia have also shifted the online learning into a hybrid one. However, conducting a hybrid class especially in relation to drama was quite challenging. Some real problems appeared and educators should be able to solve them. This article discussed those issues including some good practices to create a meaningful drama class. Data were collected through a questionnaire which included cognitive, behavioural, emotional engagement, motivation and time management. The problems covered the audibility, bad internet connection, less attention and lack of technological tool. Two of the good practices done were a dramatic reading project and gamification to facilitate students who attended the class physically or virtually.